A Methodical Review on the Applications and Potentialities of Using Nanobiosensors for Disease Diagnosis. (29th January 2022) - Ukhurebor, Kingsley Eghonghon; Onyancha, Robert Birundu; Aigbe, Uyiosa Osagie; UK-Eghonghon, Gladys; Kerry, Rout George; Kusuma, Heri Septya; Darmokoesoemo, Handoko; Osibote, Otolorin Adelaja; Balogun, Vincent Aizebeoje
Abstract : Presently, with the introduction of nanotechnology, the evolutions and applications of biosensors and/or nanobiosensors are becoming prevalent in various scientific domains such as environmental and agricultural sciences as well as biomedical, clinical, and healthcare sciences. Trends in these aspects have led to the discovery of various biosensors/nanobiosensors with their tremendous benefits to mankind. The characteristics of the various biosensors/nanobiosensors are primarily based on the nature of nanomaterials/nanoparticles employed in the sensing mechanisms. In the last few years, the identification, as well as the detection of biological markers linked with any form of diseases (communicable or noncommunicable), has been accomplished by several sensing procedures using nanotechnology vis-à-vis biosensors/nanobiosensors. Hence, this study employs a systematic approach in reviewing some contemporary developed exceedingly sensitive nanobiosensors alongside their biomedical, clinical, or/and healthcare applications as well as their potentialities, specifically for the detection of some deadly diseases drawn from some of the recent publications. Ways forward in the form of future trends that will advance creative innovations of the potentialities of nanobiosensors for biomedical, clinical, or/and healthcare applications particularly for disease diagnosis are also highlighted.